Experimental and numerical studies of PCM-based storage for solar thermal energy storage applications (Journal of Mathematics Mechanics and Computer Science, 2018)
In the world, buildings are responsible for 40% of the world’s total annual energy consumption, which is responsible for one-third of greenhouse gas emissions worldwide. The significance of this energy is used for lighting, heating, cooling and air-conditioning purposes. Raising concern about the environmental impact of greenhouse produced by conventional power plants caused renewed interest in environmentally friendly technologies, including heating and cooling systems for buildings. This work was conducted to investigate and explore the possibilities of solar energy storage using phase change materials (PCM) and using that energy to heat water for daily applications. By carrying out charging of the latent heat storage (LHS) based on PCM which is paraffin wax in the current study, its energy storage capacity was calculated and compared with the storage tank without PCM but filled with water only - sensible heat storage (SHS). As a result, LHS was able store 40% more thermal energy compared to SHS. Moreover, charging process of the LHS was numerically investigated to visualize the thermal field in the PCM based storage. The results show that the numerical results agree with the experimental results which indicated the correctness of the mathematical model and simulation results.
Keywords: latent heat storage; thermal energy storage; phase change material storage